Application of colloidal surfactants in the technology of fine-grained concrete - Shishkin А.; Shishkina А. (Ways to Improve Construction Efficiency, 2019)
The article defines the influence of colloidal surfactants on the properties of finegrained concrete. The results of experimental studies of durability under compression of fine-grained concrete in the technology of manufacture of which the methods of catalysis have been applied, which resulted in a significant increase in the strength of concrete and the speed of its formation.